2009
DOI: 10.1007/s00265-009-0857-8
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-related birdsong divergence: a multi-level study on the influence of territory density and ambient noise in European blackbirds

Abstract: Song plays an important role in avian communication and acoustic variation is important at both the individual and population level. Habitat-related variation between populations in particular can reflect adaptations to the environment accumulated over generations, but this may not always be the case. In this study, we test whether variation between individuals matches local conditions with respect to noise level and territory density to examine whether short-term flexibility could contribute to song divergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 37 publications
6
60
2
1
Order By: Relevance
“…The latter result in particular is novel in methodology and conceptual implications, as it strongly suggests the general ability to rapidly respond to fluctuating noise conditions. Although the underlying causal mechanism may vary, such an immediate spectral shift may also explain correlative patterns in other studies on other species (Slabbekoorn and Ripmeester, 2008;Bermudez-Cuamatzin et al, 2009;Parris and Schneider, 2009;Ripmeester et al, 2010). Without experimental data we are currently unable to ascribe those correlative patterns in other species to an evolutionary, ontogenetic or immediate adjustment of singing (Patricelli and Blickley, 2006) (but see Halfwerk and Slabbekoorn, Singing flexibility and highway noise 2009).…”
Section: Potential For Noise Exposure Experimentsmentioning
confidence: 96%
“…The latter result in particular is novel in methodology and conceptual implications, as it strongly suggests the general ability to rapidly respond to fluctuating noise conditions. Although the underlying causal mechanism may vary, such an immediate spectral shift may also explain correlative patterns in other studies on other species (Slabbekoorn and Ripmeester, 2008;Bermudez-Cuamatzin et al, 2009;Parris and Schneider, 2009;Ripmeester et al, 2010). Without experimental data we are currently unable to ascribe those correlative patterns in other species to an evolutionary, ontogenetic or immediate adjustment of singing (Patricelli and Blickley, 2006) (but see Halfwerk and Slabbekoorn, Singing flexibility and highway noise 2009).…”
Section: Potential For Noise Exposure Experimentsmentioning
confidence: 96%
“…The motif is made of low frequency, high amplitude melodic notes (pure tones), whereas the twitter is a final flourish composed of a burst of short, higher frequency and low amplitude notes that cover a wider frequency spectrum (Dabelsteen, 1984). Previous studies of this species show that urban blackbirds sing higher frequency motif notes (Nemeth and Brumm, 2009;Ripmeester et al, 2010). Through an increase in the frequency of this typically low-frequency part, blackbirds may improve signal transmission by reducing masking with noise, although it has been argued that higher frequency motif notes are higher in amplitude too and that the later modification should be more relevant than frequency changes to improve transmission (Nemeth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even if this implies less spectral overlap with noise it might not be a functional noise-related modification since twitter elements are usually very weak in amplitude. In fact, because of the motivational role of the twitter during male-male interactions and its seasonal variation (increasing with date), it has been suggested that larger twitter proportions are due to the increased density of territories and the advanced breeding season in urban habitats (Dabelsteen, 1984;Ripmeester et al, 2010). Blackbirds have also been found to advance the onset of dawn song when living next to urban infrastructures such as cities or airports (Nordt and Klenke, 2013;Gil et al, 2014;Dominoni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two independent studies demonstrated that city blackbirds sing on average at higher frequencies than forest birds [22,48]. Here, we applied for the first time, to our knowledge, phonetic tools to address the behavioural ecology of animal communication.…”
Section: Introductionmentioning
confidence: 99%